No- and Low-Tech Entry Points to Campus and Community Digital Humanities - López Baquero, Costanza; McCarl, Clayton; Blackin, Maya; Breede, Rook; Ferrer, Janaya; Griffith, Britney (magazén)
The digital humanities (DH) can engage students and off-campus communities with scholarly activity in new ways, reaching into extracurricular and public spaces and enabling non-specialists to participate not just as consumers but also creators. Many DH activities, however, are difficult to adapt or scale to allow for broad participation, often due to limitations in technology and training. This article examines the approaches taken by four projects at the University of North Florida to involve diverse populations both on campus and off in active roles requiring little or no technology or specialized technical abilities.